Linking Self-Efficacy to Employee Performance: Evidence from BPJS Employment Denpasar with Job Satisfaction as a Mediator - Luh Putri Swandewi; I Made Mai Noval (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the influence of self-efficacy on employee performance, with job satisfaction as an intervening variable, within the organizational setting of BPJS Ketenagakerjaan Denpasar. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationships among variables in the proposed theoretical framework. The findings reveal that self-efficacy significantly affects both job satisfaction and employee performance, directly and indirectly, through the mediating role of job satisfaction. These results underscore that self-efficacy not only enhances performance directly but also activates a psychological mechanism of job satisfaction that facilitates productive employee behavior. Within the bureaucratic context, this study contributes both conceptually and practically to human resource development strategies. Recommendations are offered to policymakers to implement efficacy-based training, internal recognition systems, and supportive leadership to foster an empowering and sustainable work environment.